Natural gas reserve/production ratio in Russia, Iran, Qatar and Turkmenistan: A political and economic perspective - ORAL, BÜLENT (ELSEVIER SCI LTD, 2016)
In this study, changes in natural gas reserve/production ratio (R/P) of the four countries having the highest natural gas reserves (Russia, Iran, Qatar, Turkmenistan), the importance of which increases in the world market each day due to developing technology and the demand for clean energy, has been analyzed depending on the economic and political developments in national and international fields. Change of R/P ratio depending on years has been displayed on graphics from different sources and these alterations have been tried to be associated with such issues as natural gas agreements in history, hand over of political authority, economic crises etc. Therefore; it has been put forward whether or not political and economic changes of the countries are factors on the amount of natural gas production and the discovery of new reserve fields with the addition aim of providing a general overview on natural gas market. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Natural gas; R/P ratio; Russia; Iran; Qatar; Turkmenistan